Effect of Total Sleep Deprivation on Visual Sequential Memory Mohammad Habibur - Azmi, Hassan; Mohammad Habibur, Rahman Khan; Salim, Hossain (2018)
A substantial number of studies support the role of sleep deprivation (SD) on sleep-dependent memory processing. Our present study investigated the effect of Total Sleep Deprivation (TSD) on Visual Sequential Memory (VSM). Two-randomized group design was followed to collect the data where experimental group (33 adults) was kept totally sleep deprived for 24 hours a day and the control group (36 adults) was not. A subtest of Test of Memory and Learning (Reynolds & Bigler, 1994) was used to measure VSM. Results revealed a significant decline in VSM for TSD (t = 3.914, p < 0.001). Findings are discussed in the light of previous findings and theories in that VSM is the capability of an individual to perceive the visual properties of an object by eyes, a skill vitally necessary for many areas of work, like visual tracking, air traffic controlling, military task, marksmanship, screening, surgery, healthcare service, policing and so on.